2019
DOI: 10.1093/molbev/msz249
|View full text |Cite
|
Sign up to set email alerts
|

HLA Heterozygote Advantage against HIV-1 Is Driven by Quantitative and Qualitative Differences in HLA Allele-Specific Peptide Presentation

Abstract: Pathogen-mediated balancing selection is regarded as a key driver of host immunogenetic diversity. A hallmark for balancing selection in humans is the heterozygote advantage at genes of the human leukocyte antigen (HLA), resulting in improved HIV-1 control. However, the actual mechanism of the observed heterozygote advantage is still elusive. HLA heterozygotes may present a broader array of antigenic viral peptides to immune cells, possibly resulting in a more efficient cytotoxic T-cell response. Alternatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 80 publications
4
75
0
1
Order By: Relevance
“…In addition, they present a greater percentage of heterozygosity. Although these findings are consistent with the bioinformatic predictions and previous works [ 13 , 21 , 24 ], these data must be interpreted with caution mainly due to the limited sample size. In this sense, global efforts are currently being made to collect samples from different types of patients, including asymptomatic individuals, in order to carry out studies with greater statistical power.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, they present a greater percentage of heterozygosity. Although these findings are consistent with the bioinformatic predictions and previous works [ 13 , 21 , 24 ], these data must be interpreted with caution mainly due to the limited sample size. In this sense, global efforts are currently being made to collect samples from different types of patients, including asymptomatic individuals, in order to carry out studies with greater statistical power.…”
Section: Discussionsupporting
confidence: 90%
“…The degree of HLA homozygosity is associated with poorer disease resistance [ 21 ]. In our study, it was found that the percentage of homozygous individuals for loci A and C was higher in the group of patients with severe evolution compared to those with moderate evolution (20% vs. 10% in locus A, 15% vs. 5% in locus C).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported genetic epidemiological observations indicating an HLA class I heterozygote advantage against HIV (32), supporting a theory originally put forth by Doherty and Zinkernagel proposing that heterozygosity at class I results in a greater repertoire of viral peptides to which an individual can respond (33). These studies are further supported by recent theoretical data (34). Thus, there are at least two mechanisms by which HLA class I genotypes can enhance the breadth of the peptide binding repertoire and protect against viral disease: heterozygosity and tapasin independence.…”
Section: Discussionsupporting
confidence: 78%
“…For example, HLA-B*46:01 that was predicted to bind to two low-affinity peptides from ORF1ab-encoded proteins, in comparison to B*15:03 and B*07:02 predicted to bind 1538 and 158 peptides derived from the same SARS-CoV-2 proteins (Fig. 4), likely supports the theory of heterozygous advantage 68 , if these HLA class I alleles express in an individual. This study provided an example of immune simulation that CD8 + T cell responses in an individual expressing a weak peptide binder HLA-B*46:01 protein can be enhanced and rescued by the heterozygous expression of B*07:02 protein, which provided complementary capacity in peptide presentation to enhance CD8 + T cell activation (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Heterozygosity of HLA alleles is considered as a result of balancing selection to shape exceptional polymorphism of HLA proteins and increase host immunocompetence against highly diverse pathogens 67,68 . In this study, HLA class I heterozygosity was demonstrated to provide an advantage in presenting additional high-affinity peptides complementarily (Figs.…”
Section: Discussionmentioning
confidence: 99%